Sosialisasi Pencegahan Infeksi Penyakit Scabies di Lingkungan Kerja - Irma Suryani Idris; Rezki Amalia; A. Bida Purnamasari; Djumarirmanto Djumarirmanto (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2024)
This Community Service activity is carried out within the Faculty of Mathematics and Natural Sciences at Makassar State University, aiming to provide an understanding of scabies, its prevention efforts, and the transmission of scabies in the work environment of cleaning service staff. Scabies is a skin disease characterized by intense itching caused by a tiny mite called Sarcoptes scabiei. The method of this Community Service Activity is conducted face-to-face, attended by 15 cleaning service personnel. The implementation of this service involves several stages, namely the preparation stage and the implementation stage. The results of this community service activity show an understanding of scabies, efforts to prevent and transmit scabies among cleaning service staff, with attention to the explanations and several questions from participants who were eager to ask.